2011
DOI: 10.1302/0301-620x.93b10.26852
|View full text |Cite
|
Sign up to set email alerts
|

Slipped capital femoral epiphysis

Abstract: We analysed the incidence of slipped capital femoral epiphysis (SCFE) in South Australia, investigating possible associations between an increased incidence of SCFE, the local indigenous population and the Australian obesity epidemic during the last 20 years. Data including race, age and gender were collected to obtain a profile of the South Australian SCFE patient, and were then compared with epidemiological data for South Australian adolescents. We concluded that the incidence of both obesity and SCFE is inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…The concerns regarding the rising incidence of SCFE relative to the increasing prevalence of obesity in children (Neovius et al 2006, Nguyen et al 2011 are not supported by this study. As a matter of fact, the incidence rate has some variation since 1978, with peaks in 1981 and 2002, but it then remains roughly the same until 2011.…”
Section: Discussioncontrasting
confidence: 59%
“…The concerns regarding the rising incidence of SCFE relative to the increasing prevalence of obesity in children (Neovius et al 2006, Nguyen et al 2011 are not supported by this study. As a matter of fact, the incidence rate has some variation since 1978, with peaks in 1981 and 2002, but it then remains roughly the same until 2011.…”
Section: Discussioncontrasting
confidence: 59%
“…This supports the finding of one previous small study (n=26) that found early BMI abnormalities in children prior to the diagnosis of SCFE, 16 and several larger series from specialist centres that report strong associations with obesity among children affected by SCFE. 12 14 15 However, only 174 children had a BMI recorded within their medical records prior to diagnosis, which may introduce a selection bias. Such individuals may have had their BMI recorded owing to a particular concern (eg, obesity), which may therefore misrepresent the cohort.…”
Section: Discussionmentioning
confidence: 99%
“…This includes patients who have Vitamin D deficiency and are of Aboriginal Australian descent. 17,18 Additionally, Shank et al have shown that coxa valga is a risk factor for valgus slips. 4 When they do occur, it is more common on the left hip.…”
Section: Discussionmentioning
confidence: 99%